Physical and Chemical Quality of Sorghum and Indigofera Silage as Cow Feeding in the Sentra Pertanian Terpadu of PT Arutmin Indonesia Tambang Asamasam - Noor Jannah; Fajri Maulana; Endang Wawan; Nurul Yakin; Muhammad Syahwal Ade Putra (Asian Journal of Social and Humanities, 2024)
To support the management of forage and cattle fattening business at the Integrated Agricultural Center (SPT) of PT Arutmin Indonesia Tambang Asamasam. This research uses the Field Work Practice (PKL) method which is carried out for three months, starting from March 4, 2024 to June 3, 2024. During this period, various activities are carried out according to a predetermined schedule and can be adjusted to other activities of the company. This street vendor was held at PT Arutmin Indonesia Tambang Asamasam, which is located in Simpang Empat Sungai Baru Village, Jorong District, Tanah Laut Regency, South Kalimantan Province. The results of this study show that Silage P3 (sorghum 40% and indigofera 60%) and P4 (sorghum 20% and indigofera 80%) are seen from physical quality (color, texture, aroma, and pH) and chemical quality, especially protein content, are in accordance with cow fattening. The physical qualities of sorghum silage and indigofera (color, texture and aroma) are almost the same very well there are no failures in the fermentation process. The pH value of silage is able to stay below 4 so that the silage is of good quality. The chemical quality of sorghum and indigofera with water content of 67.78 – 70.02%, ash content 4.03 – 6.83%, crude protein 4.69 – 19.41%, crude fat 7.58 – 9.35%, crude fiber 38.21 – 40.29%, carbohydrates 18.60 -23.59%, phosphorus 0.13 – 0.21%, calcium 0.16 – 0.91% and calories 197.27 – 228.54Cal/g can be used for cattle fattening.